2021
DOI: 10.1101/2021.01.20.427494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABA facilitates spike propagation through branch points of sensory axons in the spinal cord

Abstract: SUMMARYGABA is an inhibitory neurotransmitter that produces both postsynaptic and presynaptic inhibition. We describe here an opposing excitatory action of GABA that facilitates spike transmission at nodes of Ranvier in myelinated sensory axons in the spinal cord. This nodal facilitation results from axonal GABAA receptors that depolarize nodes toward threshold, enabling spike propagation past the many branch points that otherwise fail, as observed in spinal cords isolated from mice or rats. Activation of GABA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(55 citation statements)
references
References 168 publications
(600 reference statements)
3
52
0
Order By: Relevance
“…For decades, it was thought that sensory regulation was accomplished in part through axoaxonic contacts at the terminal of Ia sensory axons through presynaptic inhibition [10][11][12]34 . However, recent evidence in animal and humans suggest that facilitation of Ia mediated EPSPs in motor neurons likely occurs when axon nodes are depolarized from the activation of nodal GABAA receptors 14,15 . Thus, it is possible that the regulation of Ia afferent input tested in our study occurs at different sites within the Ia afferent fiber.…”
Section: Regulation Of Ia Afferent Input After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, it was thought that sensory regulation was accomplished in part through axoaxonic contacts at the terminal of Ia sensory axons through presynaptic inhibition [10][11][12]34 . However, recent evidence in animal and humans suggest that facilitation of Ia mediated EPSPs in motor neurons likely occurs when axon nodes are depolarized from the activation of nodal GABAA receptors 14,15 . Thus, it is possible that the regulation of Ia afferent input tested in our study occurs at different sites within the Ia afferent fiber.…”
Section: Regulation Of Ia Afferent Input After Scimentioning
confidence: 99%
“…For decades, it was thought sensory regulation was accomplished in part through axoaxonic contacts at the terminal of Ia sensory axons from GABAergic neurons that receive innervation from the brain and spinal cord through presynaptic inhibition [10][11][12][13] . Recent evidence in animal and humans suggested that facilitation of Ia mediated excitatory postsynaptic potentials (EPSPs) in motor neurons likely occurs when axon nodes are depolarized from the activation of nodal GABAA receptors, which contributes to reduce branch point failure in Ia afferent fibers 14,15 . Thus, GABAergic networks can have both facilitating and inhibitory actions on afferent transmission within the spinal cord at different sites within Ia afferents 16 .…”
Section: Introductionmentioning
confidence: 99%
“…106 and 107). Some of these interneurons were, in addition, found to project to the dorsal columns (102). In view of the growing evidence for nonsynaptically evoked effects of spill-over transmitters (101,(108)(109)(110)(111)(112)(113) and its volume conductance (114,115), these GABAergic interneurons could thereby contribute to changing the excitability of afferent fibers both within and ventral to the dorsal columns.…”
Section: Characteristics Of Branching Points Of Afferent Fibers At Their Entry In the Spinal Cordmentioning
confidence: 99%
“…. sodium channel clusters were smaller and more closely spaced ($6 mm apart)" (102). The estimated space constant of collaterals of group Ia afferents ($0.1 mm within their proximal compartments (102, see their Supplemental Fig.…”
Section: Characteristics Of Branching Points Of Afferent Fibers At Their Entry In the Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation